The importance of crisis management in the aviation industry: A case study on Kuwait - Abdallah, Farid; Elhoss, Walid; Chahine, Jawad (Edelweiss Applied Science and Technology, 2025)
Despite being one of the fastest-growing industries, the aviation business is infamous for difficulties affecting its operations. During the past thirty years, the airline industry has faced multiple crises that crushed passenger demand. Nonetheless, the industry was always prepared and showed resilience by emerging stronger after every crisis. However, this fact appeared to change since the COVID-19 pandemic, whereby the industry encountered an unprecedented crisis. Countries closed their borders and airspaces, thus bringing airline operations to a complete halt. Therefore, airlines deployed all their knowledge in crisis management and emergency response to operate repatriation flights and ensure preparedness to resume operations whenever the situation changes. The aim of this paper is to identify the emergency response and crisis management procedures implemented by Kuwait Airways and Kuwait Civil Aviation Authority (DGCA) during the COVID-19 crisis and assess whether those measures can be used in any similar future crisis, which can be considered as qualitative research. Data was collected using expert interviews and document analysis. The study employed data triangulation by cross-referencing insights obtained from interviews with senior personnel at Kuwait Airways and the Kuwait DGCA with official documentation published by international authorities. These findings were further validated through additional interviews with experts from the aviation industry. The study found that Kuwait's aviation sector responded effectively to the COVID-19 crisis. This paper concluded that the procedures and guidelines followed by Kuwait’s aviation sector can be replicated across different countries or country blocs taking into consideration challenges such as international collaboration and technological integration.